Capturing the electromagnetic counterparts of binary neutron star mergers through low-latency gravitational wave triggers - Chu, Q.; Howell, E.; Rowlinson, A.; Gao, H.; Zhang, B.; Tingay, Steven; Boër, M.; Wen, L. (Oxford University Press, 2016)
© 2016 The Authors. We investigate the prospects for joint low-latency gravitational wave (GW) detection and prompt electromagnetic (EM) follow-up observations of coalescing binary neutron stars (BNSs). For BNS mergers associated with short duration gamma-ray bursts (SGRBs), we for the first time evaluate the feasibility of rapid EM follow-ups to capture the prompt emission, early engine activity, or reveal any potential by-products such as magnetars or fast radio bursts. To achieve our goal, we first simulate a population of coalescing BNSs using realistic distributions of source parameters and estimate the detectability and localization efficiency at different times before merger. We then use a selection of facilities with GW follow-up agreements in place, from low-frequency radio to high-energy y-ray to assess the prospects of prompt follow-up. We quantify our assessment using observational SGRB flux data extrapolated to be within the horizon distances of the advanced GW interferometric detectors LIGO and Virgo and to the prompt phase immediately following the binary merger. Our results illustrate that while challenging, breakthrough multimessenger science is possible with EM follow-up facilities with fast responses and wide fields-of-view. We demonstrate that the opportunity to catch the prompt stage (<5s) of SGRBs can be enhanced by speeding up the detection pipelines of both GW observatories and EM follow-up facilities. We further show that the addition of an Australian instrument to the optimal detector network could possibly improve the angular resolution by a factor of 2 and thereby contribute significantly to GW-EM multimessenger astronomy.